Impoliteness in Power-imbalance and Power-neutral Relational Contexts: Evidence from a Persian TV Drama - Keshavarz, Mohammad Hossein (State institute of islamic studies salatiga, 2022)
This study investigated impoliteness in relational contexts. Interlocutors analyzed the data from a Persian TV drama from two perspectives: intentionality and perception of impoliteness. Two relational contexts were identified: power-imbalance and power-neutral, each comprising two types of impoliteness: reciprocal and non-reciprocal. Reciprocal impoliteness occurred in hostile and conflictual situations where impoliteness was both intended by the speaker and perceived by the recipient as a direct face-attack. In non-reciprocal impoliteness, however, when power imbalance was due to family hierarchy, the recipient of impoliteness remained silent; in other situations, the intentional face-attack was tolerated, unless the recipient’s social identity face was directly attacked. In power-neutral situations, impoliteness was not reciprocated when intimacy existed between the interactants. It was neither intended nor perceived as face-threatening; however, direct face-attack was reciprocal in hostile situations. The findings of the present study point to the significant role of the relational context in the interpretation of impoliteness.